Benefit of F-15 protocols in equivocal F + 20 MAG3 renography in children with upper tract dilatation and symmetric split function: Results and outcomes. Issue 5 (October 2016) - Strasser, C.; Haid, B.; Langsteger, W.; Oswald, J.
Summary: Purpose: In children with upper tract dilatation, diuretic renography, which includes application of mercaptoacetyltriglicin-99 mTc (MAG3), is the standard examination. Ordinarily, furosemide is applied 20 min after tracer injection (F + 20). In children with persistent hydronephrosis and preserved split function, this protocol may lead to further examinations with repeatedly equivocal washout curves. The present study evaluated the potential of MAG3 (F-15) scans in this subgroup of children to achieve a conclusive result avoiding additional equivocal MAG3 (F + 20) scans. Objective: To evaluate whether the washout curve using the F-15 protocol is a helpful criterion with which to clarify results in patients with equivocal patterns in the F + 20 protocol. Patients: 31 children (male/female 22/9, median age at time of examination 42 months, mean anterioposterior diameter 2.1 cm, left/right 14/18) underwent MAG3 F-15 renography at the present department because of upper urinary tract dilatation and (repeatedly n ≥ 2 F + 20 = 28) equivocal results in MAG3 F + 20 examinations. Results: In 10/31 children (32.2%), MAG3 F-15 revealed an obstructive pattern, indicating a pyeloplasty in 9/10 of them (90%). In 16/31 children (51%), the F-15 protocol showed a non-obstructive curve, leading to further uneventful follow-up in 15/16 of them (93.7%). In 5/31 children (16%), MAG3 F-15 led to equivocal results, resulting in no pyeloplasty and further uneventful follow-up in all the children (mean follow-up 1.46 years). Discussion: In children with persistent high-grade hydronephrosis on ultrasound and preserved split function, multiple scans were prompted and further management was sometimes difficult. Although there was proven evidence that the F-15 protocol reduced the frequency of equivocal pattern, there was no indication for primary F-15 investigation, due to the risk of over diagnosis of obstruction. The F-15 scan was considered to be a stress test of the upper tract leading to a diuretic challenge without any opportunity to investigate normal washout curve. In these cases, partial obstruction could lead to false positive obstructive results. A stepwise approach, in which the traditional F + 20 technique allows observation of the rate of washout of radiopharmaceuticals before forced diuresis followed by a F-15 protocol, could reduce the child's additional radiation burden and stress. Conclusion: After equivocal results in MAG3 F + 20 protocols, performing a MAG3 F-15 exam lead to a conclusive result in 80.6% (25/31 patients) of the cases. Thus, performing a MAG3 (F-15) exam can be recommended in children with persistent hydronephrosis and preserved split function after equivocal results on MAG3 (F + 20) scans.